Viewpoint Invariance of Eye Size Illusion Caused by Eyeshadow - Muto, Hiroyuki; Ide, Mayu; Tomita, Akitoshi; Morikawa, Kazunori (Frontiers in Psychology, 2019)
Previous research found that application of eyeshadow on the upper eyelids induces overestimation of eye size. The present study examined whether this eyeshadow illusion is dependent on or independent of viewpoint. We created a three-dimensional model of a female face and manipulated the presence/absence of eyeshadow and face orientation around the axis of yaw (Experiment 1) or pitch (Experiment 2) rotation. Using the staircase method, we measured perceived eye size for each face stimulus. Results showed that the eyeshadow illusion occurred regardless of face orientation around axes of both yaw and pitch rotations. Crucially, the illusion’s magnitude did not vary across face orientations; lack of interaction between the illusion’s magnitude and face orientation was confirmed by small values of Bayes factors. These findings ruled out the hypothesis that eyeshadow serves as a depth cue and leads to overestimation of eye size due to size-distance scaling. Alternatively, the present findings suggest that the eyeshadow illusion can be well explained by the assimilation between the eyes and eyeshadow, which also facilitates assimilation between the eyes and eyebrows. Practical implications and the present findings’ generalizability are also discussed.